2011
DOI: 10.13031/2013.39849
|View full text |Cite
|
Sign up to set email alerts
|

Development of Algorithms for Modeling Onsite Wastewater Systems within SWAT

Abstract: Onsite wastewater systems (OWSs) are a significant source of nonpoint-source pollution to surface and groundwater in both rural and suburban settings. Methods to quantify their effect are therefore important. The mechanics of OWS biogeochemical processes are well studied. However, tools for their assessment, especially at the watershed scale, are limited. As part of this work, modeling capabilities were developed within the Soil Water Assessment Tool (SWAT) such that OWSs and their subsequent environmental imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…According to Jeong et al [11] and Hoghooghi et al [14], the contribution of groundwater to streamflow is relatively high during dry years, similar to the research findings of this study.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…According to Jeong et al [11] and Hoghooghi et al [14], the contribution of groundwater to streamflow is relatively high during dry years, similar to the research findings of this study.…”
Section: Discussionsupporting
confidence: 90%
“…By representing the area under the septic system, using available sewer data and TN loads data, a more accurate model of anthropogenic nitrogen inputs into the Hunt River Watershed was able to be developed. This study showed the importance of groundwater contributions to streamflow and nitrogen loading and the findings are corroborated by research conducted by Jeong et al and Hoghooghi et al [11,14]. …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The SWAT model was selected because of its use of readily available input data, process-based simulation algorithms, and its open source code (Easton et al, 2008). Many previous successful modifications of the SWAT model, conducted by developers all over the world, have contributed to the model's widespread use and flexibility (e.g., Easton et al, 2008;Gassman et al, 2007;Jeong et al, 2011aJeong et al, , 2011bMoriasi et al, 2009Moriasi et al, , 2011.…”
mentioning
confidence: 99%